Turkistonda yer-suv islohotining amalga oshirilishida davlat arbobi Turor Risqulovning о‘rni (SCIENCE and SOCIETY, 2025)
The article analyzes the course of agrarian reforms in Turkestan, in particular, the reforms carried out in 1921-1922 and 1923-1924. Based on scientific sources, the initiatives of T.Ryskulov, the tasks he set in the government, and the decisions made during these reforms are assessed. The article generally reveals the practical significance of land and water reforms in Turkestan, their role in restoring social justice and ensuring economic stability, as well as the leading role of Turor Riskulov in this process.